Study of thermal cycling effect on ductile cast iron microstructure and its influence on fatigue mechanism - Lew, Ian Shao Liang (2017)
Ductile cast iron (DCI) is a commonly used material in the automotive industry. DCI has a superior fatigue due to the presence of graphite in its microstructure. In this study, the grade of ferritic ductile iron, EN-GJS-500-14, is being used. This material has mechanical properties of E = 170 GPa, yield stress of 410 MPa, Ultimate Tensile Strength (UTS) of 510 MPa and elongation of 17 %. The material was treated with inoculant and nodulizer to form spheroidal graphite and have some fraction of graphite deviation from nodular shape resulting into average nodularity by area of 74 ± 3 %. The material underwent two hundred thousand thermal cycles from room temperature (RT) to 600 °C. No initiation was observed under the scanning electron microscope (SEM). Fatigue tests were conducted on miniature tensile specimens. SEM is used to study the effect of any microstructure features on crack initiation and propagation behaviour. Defects in casting and in particular micro shrinkage porosity will cause premature fracture in the material used in this study. Crack initiation appeared first in irregular and compacted graphites. Crack is likely to cause internal cracking and then propagates into the surrounding ferrite matrix. Crack propagation is perpendicular to direction of the direction of the fatigue loading. Internal debonding into onion-liked mechanism was observed in spheroidal graphite. Crack initiation is rarely applicable for spheroidal graphite.